(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
When the development of our country has reached a high stage and the introduction of intensive agricultural technologies, the problem of increasing soil fertility and conservation is one of the most important issu es in agriculture.